Threat and Emotions: Mobilizing and Attitudinal Outcomes of a Ballistic Missile Scare. (12th November 2020) - Bergstrand, Kelly; Robertson, Christopher
Abstract: This study examines the false ballistic missile alert that occurred in Hawaii in 2018, which presented a unique opportunity for assessing the civic and mobilizing outcomes of a threat. In the days that followed the scare, we conducted an online experiment to investigate its effects on willingness to engage in activism and concerns about broader issues. Our results show that emotions serve as an important mechanism for channeling threat experiences into concern about specific causes. Those most emotionally affected by the missile scare in Hawaii thought it more important to engage in activities to control the spread of nuclear weapons, protect the environment, and address climate change, relative to a control group on the mainland. Both the intensity and type of emotion play a role. These results shed light on the role of threats and grievances in shaping concern about social and environmental issues. They also suggest that emotions may serve as a bridge that can connect personal, concrete, lived-experiences to more abstract, complex, or future-oriented issues and grievances.